Peran Edukasi Gizi Seimbang dan Pengukuran Indeks Massa Tubuh (IMT) Pada Lansia di Samarinda tahun 2024 - Simpajo, Nurul Rizkiana Tistania; Wisnuwardani, Ratih Wirapuspita; Kamaruddin, Iriyani (LPPM Universitas Pekalongan, 2025)
The quality of life of the elderly is significantly influenced by their nutritional status. Elderly individuals with good nutritional status tend to have a better quality of life, as adequate nutrition helps maintain bodily functions, strengthens the immune system, and enhances energy and mobility. This community service aimed to increase knowledge about balanced nutrition among the elderly and reduce the risk of non-communicable diseases such as obesity and malnutrition through education on balanced nutrition and health and nutritional status assessments for the elderly. Community service activities through balanced nutrition education and BMI measurement, using an interactive lecture method, showed a 30.10% increase in knowledge after education compared to before. Nutrition education has proven effective in improving the elderly’s understanding of balanced nutrition. Routine monitoring of nutritional status is highly recommended to prevent overnutrition and degenerative diseases in the elderly. Additionally, balanced nutrition education is recommended not only at the Sidomulyo Health Center but also at all health centers in Samarinda to improve the health of the elderly community more broadly.